Acquisition and Assistance Strategy - USAID - USAID (USAID, 2018)
The U.S. Agency for International Development (USAID) of tomorrow is o ne in which the Agency enables partner countries to plan, resource, an d manage their own development through strengthened capacity and commi tment — this is the essence of the Journey to Self-Reliance. In Fiscal Year (FY) 2018, the Agency obligated over 80 percent of its programma tic funding — a total of $17 billion — through acquisition and assista nce (A&A) mechanisms. Partnering and procurement are central to how we do our work. Therefore, we must think holistically about with whom we work and how we work, if we are to achieve our ambitious goals for th e USAID of tomorrow. The purpose of this document is to provide a tran sparent strategy that guides changes to Agency policy and practice for both our staff and implementing partners in how we approach our core A&A work. This strategy, which builds on previous and current reform e fforts, outlines the shifts we will make to embrace a self-reliance mo del for A&A and move concretely toward the goal of ending the need for foreign assistance. GUIDING PRINCIPLES OF PARTNERING AT USAID USAID’s partnering approaches have evolved significantly over time as we have tested new and innovative ways of working. The principles outlined be low support the Journey to Self-Reliance by empowering our staff and p artners to produce results-driven solutions responsive to partner coun try needs and priorities — building capacity and commitment based on c reative and entrepreneurial approaches that have already begun to deve lop. The Agency must move beyond our traditional approaches to embrace greater collaboration, co-design, and co-financing to improve upon ou r models of partnering.